KARAKTERISTIK SARI BUAH SALAK VARIETAS NANGKA (Salacca zalacca Var. ambonesnsis) PADA PENAMBAHAN JENIS DAN KONSENTRASI PENSTABIL - Putra Simanullang, Yohannes Eko; Gunam, Ida Bagus Wayan; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 1 (2019): MaretDO - 10.24843/JRMA.2019.v07.i01.p11, 2019)
The purpose of this study is to determine the type and concentration of stabilizers used in the functional drinks of salak juice and determine the type and concentration of stabilizers to produce the best characteristic salak juice. The main research aims to determine the type and concentration of stabilizers that product of salak juice. Primary research carried out by using a randomized block design (R BD) consisting of two factors The stabilizers used in this reseach that CMC, arabic gum, and gelatin. Concentration of the stabilizers used was 0.10%, 0.15%, 0.20% and 0.25%. The results showed that the type of stabilizers, concentration of stabilizers and interaction affected on the characteristics of functional fruit salak juice. The type and stabilizer concentration had an effect on total dissolved solids, viscosity, total sugar, stability, color scoring test, taste scoring test, aroma scoring test, and overall acceptance, but did not affect pH and total acid. The CMC stabilizer with a concentration of 0.25% is the best treatment for producing salak juice with characteristics of pH 4.12, total dissolved solids 13.60 o Brix, total acid 0.58%, viscosity 32.0cP, total sugar 2.45%, stability with absorbance 0.580A, the color scoring rate was 3.85 (transparan yellow-pale yellow), the scoring rate was 3.80 (normal-specific), the level of aroma was 3.70 (normal-specific) and the level of overall accepted was 3.70 (normal – like). Keywords : Salak  juice, Stabilizer s, Concen tr ation , CMC, gelatin, gum arab